PENGARUH IN STORE DIGITAL EXPERIENCE DAN FEAR OF MISSING OUT (FOMO) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN RITEL MODERN PADA INDOMARET - Fabillah Khoirunisa; Nuzulia Ashar; M. Rifki Bakhtiar (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of In-Store Digital Experience and Fear of Missing Out (FOMO) on Purchase Decisions among Modern Retail Consumers at Indomaret. This research employed a quantitative approach involving 172 respondents selected through a purposive sampling technique based on predetermined criteria. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of IBM SPSS software. The finding show that In-Store Digital Experience has a positive and significant effect on Purchase Decisions. Furthermore, Fear of Missing Out (FOMO) also has a positive and significant effect on Purchase Decisions. The simultaneous testing indicates that In-Store Digital Experience and FOMO jointly exert a positive and significant influence on Purchase Decisions. The coefficient of determination (R²) of 0.462 indicates that the two independent variables explain 46.2% of the variation in Purchase Decisions, while the remaining 53.8% is attributable to other factors beyond the scope of this study. These findings highlight the importance of enhancing the in-store digital experience and understanding consumers' psychological factors in order to encourage more effective purchase decisions among modern retail consumers at Indomaret.